Targeted mutagenesis in tetraploid switchgrass (Panicum virgatum L.) using CRISPR/Cas9. Issue 2 (1st August 2017) - Liu, Yang; Merrick, Paul; Zhang, Zhengzhi; Ji, Chonghui; Yang, Bing; Fei, Shui‐zhang
Summary: The CRISPR/Cas9 system has become a powerful tool for targeted mutagenesis. Switchgrass ( Panicum virgatum L.) is a high yielding perennial grass species that has been designated as a model biomass crop by the U.S. Department of Energy. The self‐infertility and high ploidy level make it difficult to study gene function or improve germplasm. To overcome these constraints, we explored the feasibility of using CRISPR/Cas9 for targeted mutagenesis in a tetraploid cultivar 'Alamo' switchgrass. We first developed a transient assay by which a non‐functional green‐fluorescent protein gene containing a 1‐bp frameshift insertion in its 5′ coding region was successfully mutated by a Cas9/sgRNA complex resulting in its restored function. Agrobacterium ‐mediated stable transformation of embryogenic calli derived from mature caryopses averaged a 3.0% transformation efficiency targeting the genes of teosinte branched 1(tb1)a and b and phosphoglycerate mutase ( PGM ). With a single construct containing two sgRNAs targeting different regions of tb1a and tb1b genes, primary transformants (T0) containing CRISPR/Cas9‐induced mutations were obtained at frequencies of 95.5% ( tb1a ) and 11% ( tb1b ), respectively, with T0 mutants exhibiting increased tiller production. Meanwhile, a mutation frequency of 13.7% was obtained for the PGM gene with a CRISPR/Cas9 construct containing a single sgRNA. Among the PGM T0 mutants, six are heterozygous and one is homozygous for a 1‐bp deletion in the target region with no apparent phenotypical alterations. We show that CRISPR/Cas9 system can generate targeted mutagenesis effectively and obtain targeted homozygous mutants in T0 generation in switchgrass, circumventing the need of inbreeding.